Initial Estimates on the Performance of the LSST on the Detection of Eclipsing Binaries. (4th May 2017) - Wells, Mark; Prs̆a, Andrej; Jones, Lynne; Yoachim, Peter
Abstract: In this work, we quantify the performance of the Large Synoptic Survey Telescope ( LSST ) on the detection of eclipsing binaries. We use Kepler observed binaries to create a large sample of simulated pseudo- LSST binary light curves. From these light curves, we attempt to recover the known binary signal. The success rate of period recovery from the pseudo- LSST light curves is indicative of LSST 's expected performance. Using an off-the-shelf analysis of variance routine, we successfully recover 71% of the targets in our sample. We examine how the binary period impacts recovery success and see that for periods longer than 10 days, the chance of successful binary recovery drops below 50%.